General practitioners’ involvement during survivorship care of colon cancer in the Netherlands: primary health care utilization during survivorship care of colon cancer, a prospective multicentre cohort study - Duineveld, Laura A M (Fam Pract, 2019)
BACKGROUND: Primary health care use increases when cancer is diagnosed. This increase continues after cancer treatment. More generalist care is suggested to improve survivorship care. It is unknown to what extent cancer-related symptoms are currently presented in primary care in this survivorship phase. OBJECTIVE: To analyse primary health care utilization of colon cancer patients during and after treatment with curative intent. METHODS: In a prospective multicentre cohort study among patients with curatively treated colon cancer, we describe the primary health care utilization during the first 5 years of follow-up. Data were collected at general practitioner (GP) practices during 6 months. RESULTS: Of 183 included participants, 153 (84%) consulted their GP resulting in 606 contacts (mean 3.3, standard deviation 3.01) with on average 0.9 contact for colon-cancer-related (CCR) problems in the 6-month study period. Median time after surgery at inclusion was 7.6 months (range 0–58). Abdominal pain and chemotherapy-related problems were the most frequently reported CCR reasons. Of the CCR contacts, 83% was managed in primary care. As time after surgery passed, the number of CCR contacts declined in patients without chemotherapy and remained constant in patients who received chemotherapy. CONCLUSION: Colon cancer survivors contact their GP frequently also for reasons related to cancer. Currently, a formal role for GPs in survivorship care is lacking, but nevertheless GPs provide a substantial amount of care. Working agreements between primary and secondary care are necessary to formalize the GP’s role in order to improve the quality of survivorship care.